2013
DOI: 10.1039/c3dt32657h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural characterization and catalytic evaluation of the ring-opening polymerization of discrete five-coordinate alkyl aluminium complexes

Abstract: Five-coordinate alkyl aluminium complexes [AlR(κ(2)-pbpam)2] (R = Me 1, Et 2), [AlR(κ(2)-sbpam)2] (R = Me 3, Et 4) and [AlR{κ(2)-(S)-mbpam}2] (R = Me 5, Et 6), -pbpam [pbpam = N-phenyl-2,2-bis(3,5-dimethylpyrazol-1-yl)acetamidate], sbpam [sbpam = N-sec-butyl-2,2-bis(3,5-dimethylpyrazol-1-yl)acetamidate] and (S)-mbpam [(S)-mbpam = (S)-(-)-N-α-methylbenzyl-2,2-bis(3,5-dimethylpyrazol-1-yl)acetamidate] were obtained by an alkane elimination route involving the reaction of the previously reported acetamide heteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…On the other hand, the catalytic activities of ethyl derivatives 2 and 4 are slightly higher than the methyl complexes 1 and 3 which have been previously observed for scorpionate aluminum complexes. 53,55,58 Finally, a reaction control using TBAB as a catalyst showed that the cocatalyst by itself could catalyze the reaction but less efficiently. NMR studies confirmed that the presence of TBAB is crucial in order to increase the selectivity toward the synthesis of polyester (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the catalytic activities of ethyl derivatives 2 and 4 are slightly higher than the methyl complexes 1 and 3 which have been previously observed for scorpionate aluminum complexes. 53,55,58 Finally, a reaction control using TBAB as a catalyst showed that the cocatalyst by itself could catalyze the reaction but less efficiently. NMR studies confirmed that the presence of TBAB is crucial in order to increase the selectivity toward the synthesis of polyester (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…When these systems were employed for the ROP of rac-lactide, best conversions were achieved at 110 °C with the ratio 100:1:1 (rac-LA:Al:BnOH) over 12 h. For organoaluminium systems, the ROP of lactide often requires more robust conditions than those employed for ε-CL [32]. However, there was no clear evidence of an enhanced performance for the tetranuclear versus the dinuclear systems.…”
Section: Organoaluminium Complexesmentioning
confidence: 94%
“…However, there was no clear evidence of an enhanced performance for the tetranuclear versus the dinuclear systems. For the latter, the ethyl derivatives were slightly more active than the methyl derivatives; the same When these systems were employed for the ROP of rac-lactide, best conversions were achieved at 110 • C with the ratio 100:1:1 (rac-LA:Al:BnOH) over 12 h. For organoaluminium systems, the ROP Catalysts 2017, 7, 165 6 of 11 of lactide often requires more robust conditions than those employed for ε-CL [32]. However, there was no clear evidence of an enhanced performance for the tetranuclear versus the dinuclear systems.…”
Section: Organoaluminium Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, development of efficient synthetic strategies becomes of great interest to chemists. Among these strategies, ring-opening polymerization (ROP) catalyzed by the less toxic and inexpensive aluminum complexes is one of the useful and well-controlled methods [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30]. The ring-opening polymerization catalyzed by an organometallic complex usually proceeds through a coordination-insertion mechanism [31,32].…”
Section: Introductionmentioning
confidence: 99%